Clustering, Spatial Distribution, and Phosphorylation of Discoidin Domain Receptors 1 and 2 in Response to Soluble Collagen I. Issue 2 (18th January 2019) - Yeung, David A.; Shanker, Nirvan; Sohail, Anjum; Weiss, Brent A.; Wang, Carolyn; Wellmerling, Jack; Das, Subhadip; Ganju, Ramesh K.; Miller, Jeanette L.C.; Herr, Andrew B.; Fridman, Rafael; Agarwal, Gunjan
Abstract: Discoidin domain receptors (DDR1 and DDR2) are receptor tyrosine kinases that signal in response to collagen. We had previously shown that collagen binding leads to clustering of DDR1b, a process partly mediated by its extracellular domain (ECD). In this study, we investigated (i) the impact of the oligomeric state of DDR2 ECD on collagen binding and fibrillogenesis, (ii) the effect of collagen binding on DDR2 clustering, and (iii) the spatial distribution and phosphorylation status of DDR1b and DDR2 after collagen stimulation. Studies were conducted using purified recombinant DDR2 ECD proteins in monomeric, dimeric or oligomeric state, and MC3T3-E1 cells expressing full-length DDR2-GFP or DDR1b-YFP. We show that the oligomeric form of DDR2 ECD displayed enhanced binding to collagen and inhibition of fibrillogenesis. Using atomic force and fluorescence microscopy, we demonstrate that unlike DDR1b, DDR2 ECD and DDR2-GFP do not undergo collagen-induced receptor clustering. However, after prolonged collagen stimulation, both DDR1b-YFP and DDR2-GFP formed filamentous structures consistent with spatial re-distribution of DDRs in cells. Immunocytochemistry revealed that while DDR1b clusters co-localized with non-fibrillar collagen, DDR1b/DDR2 filamentous structures associated with collagen fibrils. Antibodies against a tyrosine phosphorylation site in the intracellular juxtamembrane region of DDR1b displayed positive signals in both DDR1b clusters and filamentous structures. However, only the filamentous structures of both DDR1b and DDR2 co-localized with antibodies directed against tyrosine phosphorylation sites within the receptor kinase domain. Our results uncover key differences and similarities in the clustering abilities and spatial distribution of DDR1b and DDR2 and their impact on receptor phosphorylation. Graphical Abstract: Unlabelled Image Highlights: Clustering, spatial distribution, and phosphorylation of collagen receptor DDR2 are examined and compared with DDR1b. Oligomerization of DDR2 ectodomain enhances collagen binding and inhibition of collagen I fibrillogenesis. While DDR1b rapidly clusters upon interaction with non-fibrillar collagen I, DDR2 does not undergo ligand-induced clustering. Upon prolonged collagen stimulation, both DDR1b and DDR2 assemble into filamentous structures, which are contiguous with and anchor collagen fibrils. Higher-order assembly of DDRs into clusters and/or filamentous structures may be a prerequisite for receptor phosphorylation at defined Tyr residues.